2004
DOI: 10.1029/2003je002196
|View full text |Cite
|
Sign up to set email alerts
|

Regional drainage of meltwater beneath a Hesperian‐aged south circumpolar ice sheet on Mars

Abstract: [1] Five sinuous valleys that begin near the margins of the Hesperian-aged Dorsa Argentea Formation (DAF) are examined using Mars Global Surveyor Mars Orbiter Laser Altimeter data. These valleys are carved into the surrounding Noachian cratered terrain and extend away from the DAF for lengths up to 1600 km before terminating in the Argyre basin 1-3 km below their starting elevations. The association of these valleys with the DAF, thought to be the volatile-rich deposits of a previously widespread circumpolar i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 24 publications
0
28
0
Order By: Relevance
“…Head (2000, 2001) identified possible kames, kettles, and eskers in the circumpolar regions. Head and Pratt (2001) and Ghatan and Head (2004) described putative meltwater drainage valleys and eskers in the southern circumpolar regions. Esker-like features have also been described in the Argyre basin (Carr and Evans, 1980;Howard, 1981;Kargel and Strom, 1992;Hiesinger and Head, 2002); Banks et al (2009) analyzed these landforms with higher spatial resolution data, confirming that they are most consistent with glacial eskers.…”
Section: Glacial Landformsmentioning
confidence: 99%
“…Head (2000, 2001) identified possible kames, kettles, and eskers in the circumpolar regions. Head and Pratt (2001) and Ghatan and Head (2004) described putative meltwater drainage valleys and eskers in the southern circumpolar regions. Esker-like features have also been described in the Argyre basin (Carr and Evans, 1980;Howard, 1981;Kargel and Strom, 1992;Hiesinger and Head, 2002); Banks et al (2009) analyzed these landforms with higher spatial resolution data, confirming that they are most consistent with glacial eskers.…”
Section: Glacial Landformsmentioning
confidence: 99%
“…Sinuous ridges have been identified at a number of sites on Mars (e.g., Williams, 2007), including on large-scale alluvial fans (Moore and Howard, 2005), on several plateaus surrounding the Valles Marineris canyon system (LeDeit et al, 2010;Weitz et al, 2010), in Sinus Meridiani and Arabia Terra (e.g., Edgett, 2005;Williams and Chuang, 2012), in the Argyre basin, (Kargel and Strom, 1992), near the south pole (e.g., Kargel, 1993;Head, 2000aHead, , 2000bHead and Pratt, 2001;Ghatan and Head, 2004), as part of a fan-shaped complex within Eberswalde crater (Malin and Edgett, 2003;Moore et al, 2003), on an alluvial fan near the Mars Science Laboratory landing site in Gale crater (Anderson and Bell, 2010), and in Aeolis Dorsa (Burr et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Particularly debris fl ows found on lee slopes of pristine windgenerated mega sand dunes must have formed in water, as inferred from heights of levees in inner and outer bends of the debris fl ow channels by modelling transverse fl ow surface gradient and viscosity (Mangold et al, 2003), similar to debris fl ows found on terrestrial alluvial fans, e.g. on Svalbard, Norway, and Dry Valley, USA Alluvial fans have surface gradients between 0·02-0·1, probably formed by dilute and/or dense water-sediment fl ows ) Lake deltas with surface gradients >0·01 and, often, a steep lee-side slope, probably formed by dilute water-sediment fl ows or perhaps as fans that were subsequently eroded at their toes (Grin and Cabrol, 1997;Ori et al, 2000;Irwin et al, 2005;Hauber et al, 2009;Kraal et al, 2008) probably formed in association to (rock) glaciers (see Baker, 2001, for review), (Neukum et al, 2004) as well as a collapsing ice sheet (Ghatan and Head, 2004) Kettle holes and frost polygons found on likely ice-margins (Lane and Christensen, 2000;van Gasselt et al, 2005) and associated with many other ice-margin lake features Ghatan and Head (2004); Dickson and Head (2006) Pingos and surface ice some pingos are still uncollapsed indicating presence of near-surface ice (Dundas et al, 2008), and fractured surface ice is protected against sublimation by dust cover (Fig. 4) (Murray et al, 2005) At present, some of the martian water is stored in the soil mantle of Mars as ground ice ( Figure 4) and mixtures of water and carbon dioxide ice (Longhi, 2006).…”
Section: Smoking Guns For Watermentioning
confidence: 98%
“…The polar caps are much thinner than on Earth and shrink and grow with the seasons. The circumpolar basin harbours sinuous meltwater valleys, eskers and kettle holes (Ghatan and Head, 2004;Dickson and Head, 2006). Mega-outfl ow channels are directed off the Tharsis height.…”
Section: Figurementioning
confidence: 99%